2013
DOI: 10.5755/j01.erem.64.2.1951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxic Effects and Bioaccumulation of Cadmium and Copper in Spring Barley (Hordeum vulgare L.)

Abstract: This paper deals with the analysis of toxic effects of cadmium and copper on the growth of spring barley (Hordeum vulgare L.) cultivated in hydroponics. The seedlings of barley were treated with four different concentrations of cadmium and copper, ranging from 0.1 to 10 mg L-1. The aim of the study was to assess toxic effects of cadmium (Cd) and copper (Cu) on the growth of spring barley, and to determine metal accumulation in above-ground and underground parts of the plant. The impact of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Being a result of membrane lipid peroxidation, MDA is often considered an indicator of membrane peroxidation and oxidative stress level [27]. Such significant relationships between single metals and MDA content were also observed by Zaltauskaite and Sliumpaite [45] in barley shoots for Cu, by Wu and Zhang [40] in barley roots, and by Shaw [5] in Phaseolus aureus for Cd. In addition, a direct relationship between MDA level and physiological response was observed for the single metals.…”
Section: Discussionmentioning
confidence: 86%
“…Being a result of membrane lipid peroxidation, MDA is often considered an indicator of membrane peroxidation and oxidative stress level [27]. Such significant relationships between single metals and MDA content were also observed by Zaltauskaite and Sliumpaite [45] in barley shoots for Cu, by Wu and Zhang [40] in barley roots, and by Shaw [5] in Phaseolus aureus for Cd. In addition, a direct relationship between MDA level and physiological response was observed for the single metals.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Cd inhibits root growth more promptly than shoot growth (Vitoria et al, 2001). Hence, Cd addition reduced the shoot fresh and dry weight also have been studied previously in different plant species such as wheat (Mane et al, 2010) and barley (Zaltauskaite and Sliumpaite, 2013). Cadmium may impede with nutrient uptake due to competition for the same transmembrane carriers, thereby leading to the altered tissue nutrient contents (Connolly et al, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…Of the total metal accumulation in plant, ≈94% Pb, ≈82% Cd, and ≈64% As were concentrated in roots only, advocates an existence of different metal sequestration mechanism, which hampered the metal translocation from root to the aboveground plant parts. Several studies [Guo et al, 2007;Karimi et al, 2013;Žaltauskaitė and Šliumpaitė, 2013] had confirmed hyper-accumulation of Cd into barley roots, could partly be explained by the Cd-loading into cell vacuole as non-active form and immobilization by cell wall [Vassilev et al, 2002]. Phytoaccumulation of Pb into above-ground plant parts is principally rare due to low solubility of most Pb-compounds, and ready precipitation of Pb by sulphate and phosphate at root system [Dushenkov et al, 1995;McGrath et al, 2002].…”
Section: Metal Accumulation Into the Plant Partsmentioning
confidence: 99%